Effect of university imagen on academic satisfaction of university students - Ccorisapra Quintana, Jeferson (2022)
In recent decades, higher education universities have faced a series of difficulties in brand positioning, satisfaction and loyalty. Therefore, the positive image that a university offers to the market is considered a crucial factor for potential and current consumers to purchase its services and ensure its sustainability in the face of the growing demand for professional training institutions. In addition, the image that students perceive of an institution is fundamental for their loyalty and academic satisfaction. In this sense, the purpose of this study was to examine the incidence of university image on the academic satisfaction of university students. A quantitative approach was used to corroborate the hypothesis, with a convenience population of 166 undergraduate university students pursuing virtual studies. Participant information was collected by means of a self-administered survey and an online questionnaire. In addition, the data followed a normal distribution corroborated by the Kolmogorov-Smirnov test and the hypothesis was tested by applying simple linear regression of SPSS version 27 statistical software. The result of the linear regression presented a coefficient of determination (R2 = 0.611) that supports that university image has a positive impact on the academic satisfaction of university students. This means that the positive image of a university generates comfort and well-being in the academic experience that students have while pursuing higher education.